G4 Sensing Pyridyl‐Thiazole Polyamide Represses c‐KIT Expression in Leukemia Cells. Issue 33 (5th May 2021) - Paul, Raj; Dutta, Debasish; Das, Tania; Debnath, Manish; Dash, Jyotirmayee
Abstract: Specific sensing and functional tuning of nucleic acid secondary structures remain less explored to date. Herein, we report a thiazole polyamide TPW that binds specifically to c‐KIT1 G‐quadruplex (G4) with sub‐micromolar affinity and ∼1 : 1 stoichiometry and represses c‐KIT proto‐oncogene expression. TPW shows up to 10‐fold increase in fluorescence upon binding with c‐KIT1 G4, but shows weak or no quantifiable binding to other G4s and ds26 DNA . TPW can increase the number of G4‐specific antibody (BG4) foci and mark G4 structures in cancer cells. Cell‐based assays reveal that TPW can efficiently repress c‐KIT expression in leukemia cells via a G4‐dependent process. Thus, the polyamide can serve as a promising probe for G‐quadruplex recognition with the ability to specifically alter c‐KIT oncogene expression. Abstract : A pyridyl bis‐thiazole, TPW preferentially binds to c‐KIT1 G‐quadruplex over other G‐quadruplexes and duplex DNA and emits high fluorescence inside cell nuclei. Despite being less toxic, it represses c‐KIT transcription in cancer cells. These unique properties of TPW could be useful for the detection of G‐quadruplexes and nuclear labeling of cancer cells.